Body Mass Index Influences the Prognostic Impact of Combined Nuclear Insulin Receptor and Estrogen Receptor Expression in Primary Breast Cancer - Björner, Sofie; Rosendahl, Ann H.; Simonsson, Maria; Markkula, Andrea; Jirström, Karin; Borgquist, Signe; Rose, Carsten; Ingvar, Christian; Jernström, Helena (Frontiers in Endocrinology, 2017)
The prognostic importance of tumor-specific nuclear insulin receptor (InsR) expression in breast cancer is unclear, while membrane and cytoplasmic localization of InsR is better characterized. The insulin signaling network is influenced by obesity and may interact with the estrogen receptor α (ER) signaling. The purpose was to investigate the interplay between nuclear InsR, ER, body mass index (BMI), and prognosis. Tumor-specific expression of nuclear InsR was evaluated by immunohistochemistry in tissue microarrays from 900 patients with primary invasive breast cancer without preoperative treatment, included in a population-based cohort in Sweden (2002-2012) in relation to prognosis. Patients were followed for up to 11 years during which 107 recurrences were observed. Nuclear InsR+ expression was present in 214 patients (23.8%) and increased with longer time between surgery and staining (P<0.001). There were significant effect modifications by ER status and BMI in relation to clinical outcomes. Nuclear InsR+ conferred higher recurrence-risk in patients with ER+ tumors, but lower risk in patients with ER- tumors (Pinteraction=0.003). Normal-weight patients with nuclear InsR+ tumors had higher recurrence-risk, while overweight or obese patients had half the recurrence-risk compared to patients with nuclear InsR- tumors (Pinteraction=0.007). Normal-weight patients with a nuclear InsR-/ER+ tumor had the lowest risk for recurrence compared to all other nuclear InsR/ER combinations (HRadj 0.50, 95% CI: 0.25-0.97), while overweight or obese patients with nuclear InsR-/ER- tumors had the worst prognosis (HRadj 7.75, 95% CI: 2.04-29.48). Nuclear InsR was more prognostic than ER among chemotherapy-treated patients. In summary, nuclear InsR may have prognostic impact among normal-weight patients with ER+ tumors and in overweight or obese patients with ER- tumors. Normal-weight patients with nuclear InsR-/ER+ tumors may benefit from less treatment than normal-weight patients with other nuclear InsR/ER combinations. Overweight or obese patients with nuclear InsR-/ER- tumors may benefit from more tailored treatment or weight management.